Enantioselective behavior analysis of chiral fungicide tetraconazole in apples with UPLC-MS/MS. (October 2020) - Li, Ye; Nie, Jiyun; Chang, Weixia; Xu, Guofeng; Farooq, Saqib; Liu, Mingyu; Zhang, Jia
Abstract: Chiral fungicide tetraconazole is widely used for apple production without the knowledge of its stereoselective degradation in apples based on the regional disparity and bagging of fruit technique. The present study was initiated to explore the stereoselective degradation of tetraconazole in Fuji apple from the three major apple-producing regions in China, with bagging and non-bagging of fruit treatments. A highly sensitive and efficient chiral separation method was developed for the analysis of tetraconazole enantiomers by UPLC-MS/MS with a Lux Cellulose-2 column. A considerable improvement was obtained for the retention time (<4 min), which reduced at least 70% as compared with previous researches. The persistence of tetraconazole stereoisomers in apples was prolonged with bagging treatment ( T 1/2, 33.94–64.49 days) than non-bagging treatment ( T 1/2, 11.88–39.79 days) in the three regions. The results indicated that the half-lives of tetraconazole enantiomers were significantly different in apples among the three regions (P < 0.01) with non-bagging of fruit treatment, while no obvious differences were found with bagging treatment between the three regions. The stereoselective dissipation of tetraconazole enantiomers in apples was not statistically different under non-bagging treatment, however, there were significant differences in degradation between enantiomers with bagging treatment (P < 0.05), in which (−)-S-tetraconazole degraded faster than (+)-R-tetraconazole in the three regions. Such behaviors of chiral pesticides should be regularly monitored due to its effects on the safety of food and risk assessment of pesticides, as well as the environmental pollution assessment. Highlights: Optimization of the enantiomeric separation method of chiral tetraconazole. Stereoselective determination and separation of tetraconazole in apple. The effect of the bagging technique on the stereoselective degradation of tetraconazole. Analysis of stereoselective degradation of tetraconazole based on the regional disparity.